Karakteristik minuman serbuk berbasis bunga lokal dengan menggunakan metode foam mat drying - Saswati Saswati; Ngatirah Ngatirah; Muhammad Prasanto Bimantio (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
This research is about local flower-based powder drinks using the Foam mat drying method. This research aims to determine the effect of the type of flower used and the ratio of flowers to water on the characteristics of local flower-based powder drinks and to determine the type of flower and the ratio of flowers to water that produces the powder drink that the panelists like most. The experimental design used in this research was a Randomized Complete Block Design (RCBD) with 2 factors including the type of flower used which consisted of 3 levels, namely A1= 100% hibiscus flowers, A2= 100% chrysanthemum flowers, A3= chrysanthemums and hibiscus flowers ( 1:1), and the ratio factor for the concentration of flowers and water which consists of 3 levels, namely B1= 1 1 (250 gr of flowers: 250 ml of water), B2= 1 : 2 (250 gr of flowers: 500 ml of water), B3= 1 : 3 (250 gr flowers: 750 ml water). The analyzes carried out in this research were water content, ash content, antioxidant activity, solubility, dissolution time, flavonoids, total phenol, organolpetic tests, total color, yield. The type of flower used in this research had an effect on antioxidants, dissolution time, organoleptics (color, aroma), flavonoids and total phenols, but had no effect on water content, ash content, solubility, yield, total color. The ratio of flowers to water has an effect on antioxidants, dissolution time, organoleptics (color, aroma), flavonoids and total phenols, but has no effect on water content, ash content, solubility, yield, and total color. Based on the overall test level of preference for both powder and brew, the panelists liked the most in the A1B1 treatment which used hibiscus flowers with a flower to water ratio (1:1) with a preference level of 4.39 for the powder and 4.35 for the brew.